High‐dose oral colecalciferol loading in obesity: impact of body mass index and its utility prior to bariatric surgery to treat vitamin D deficiency. Issue 2 (1st February 2017) - King, R. J.; Chandrajay, D.; Abbas, A.; Orme, S. M.; Barth, J. H.
Summary: Obesity is associated with lower vitamin D levels compared with normal weight subjects, and if levels are not replaced prior to bariatric surgery, this can increase fracture risk as bone density typically falls post‐operatively. We analysed the effect of body mass index (BMI) on vitamin D levels in response to 300 000 IU of colecalciferol in patients with vitamin D deficiency (<30 nmol L −1 ). Patients were grouped according to their BMI as normal weight (20–24.9 kg m −2 ), overweight (25–29.9 kg m −2 ), obese class I (30–34.9 kg m −2 ) and obese class II and above (>35 kg m −2 ). The records were retrospectively analysed to investigate the effects of BMI on vitamin D (total 25‐hydroxy vitamin D [25(OH)D]), serum Ca 2+ and parathyroid hormone (PTH) levels at 6, 12, 26 and 52 weeks compared with baseline. Compared with normal weight subjects, overweight and obese patients achieved lower mean peak total 25(OH)D levels (6 weeks post‐loading), which was most significant in the class II and above group (mean total 25(OH)D levels 96.5 ± 24.2 nmol L −1 and 72.42 ± 24.9 nmol L −1, respectively; P = 0.003). By 26 weeks, total 25(OH)D levels fell in all groups; however, there was now a significant difference between the normal weight subjects and all other groups (mean total 25(OH)D levels 84.1 ± 23.7 nmol L −1 ; 58 ± 20 nmol L −1, P = 0.0002; 62.65 ± 19.2 nmol L −1, P = 0.005; 59.2 ± 21 nmol L −1, P = 0.005, respectively). Far fewer patients in the overweight and obese groups maintained levels above the recommended level of 75 nmol L −1 52 weeks post‐loading (93%; 20%, P = 0.0003; 23%, P = 0.01; and 14%, P = 0.001, respectively). Alternative regimes for the treatment of vitamin D deficiency are needed in overweight and obese patients, especially those in whom bariatric surgery is planned.